Production of gasoline octane booster aromatics benzene, toluene and ethylbenzene from multiphase catalytic pyrolysis of mixed waste expanded polystyrene and high density polyethylene - Verma A.; Pramanik H. (My University, 2025)
The main objective of this study is to enhance the valuable octane booster aromatics benzene, toluene, and ethylbenzene (BTE) and reduction of styrene in the fuel oil obtained from the pyrolysis of equally mixed waste expanded polystyrene (WEPS) and waste high density polyethylene (WHDPE). This research article, demonstrated the pyrolysis of equally mixed (50 wt.%:50 wt.%) waste expanded polystyrene (WEPS) and waste high-density polyethylene (WHDPE) followed by in situ-hydrogenation and aromatization in a small laboratory scale reactor for the production of value added commodity and gasoline octane boosters mainly benzene, toluene, and ethylbenzene (BTE). Three reactor arrangements i.e., liquid phase/L-type, vapour phase/V-type, and multiphase/M-type were used for conducting the catalytic pyrolysis of feedstock using ZSM-5, ammonium powder as a catalyst. The maximum liquid yield of 87.41 wt.% was obtained for thermal pyrolysis at a temperature of 650°C and at a heating rate of 15°C/min. Whereas, the maximum liquid yield of 82.65 wt.% was obtained for liquid phase/L-type catalytic pyrolysis at a temperature of 600°C, and at a heating rate of 15°C/min. On the other side, vapour phase/V-type and multiphase/M-type catalytic pyrolysis produced a maximum liquid yield of 78.62 wt.% and 74.07 wt.%, respectively at a reaction temperature of 550°C and at the same heating rate. The pyrolysis oil obtained from thermal pyrolysis contained lowest BTE content of 10.43 wt.% and highest styrene content of 66.25 wt.%. Whereas, the highest BTE content of 30.16 wt.% and lowest styrene content of 53.32 wt.% was found in pyrolysis oil obtained from multiphase/M-type catalytic pyrolysis. The quantitative measurement of BTE and styrene content in the pyrolysis oil was made by the gas chromatography (GC) in a flame ionization detector (FID) mode. © The Author(s) 2023.